The Implementation of Interactive Learning through the Hypnoteaching Method in Fostering Children's Emotional Intelligence at PAUD Nurul Furqon - Hadijah; Ihlas; Ade S Anhar (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of interactive learning through the hypnoteaching method in fostering emotional intelligence among early childhood learners at PAUD Nurul Furqon. Emotional intelligence is a crucial aspect of early childhood development, as it influences children’s ability to recognize and manage emotions, develop empathy, and engage in positive social interactions. This research employed a qualitative descriptive approach involving 15 children and 2 teachers at PAUD Nurul Furqon. Data were collected through classroom observations, interviews with teachers, and documentation of learning activities. The findings show that the implementation of the hypnoteaching method was characterized by the use of positive suggestions, empathetic communication, and warm interactions that created a conducive and emotionally supportive learning environment. Observation and interview data revealed that children were more actively involved in learning activities, demonstrated emotional awareness, expressed empathy toward peers, and engaged in positive social interactions during the learning process. The study concludes that the implementation of interactive learning through the hypnoteaching method reflects learning practices that support the development of children’s emotional awareness, empathy, self-regulation, and social interaction skills within the context of early childhood education.